Exploring Essential Skills for Sustainable Community Leadership: A Data Analysis Perspective on SDGs Alignment and Model - Pigultong, Matee (Bright Publisher, 2024)
This research explores the essential skills required by Thai Buddhist moral teacher monks as community leaders for sustainable development. These monks, representing Buddhism, play a crucial role in conserving teachings and fostering spiritual well-being. The study, employing mixed methods, identifies a comprehensive set of 17 skills necessary for their leadership roles, ranging from academic coordination to digital media- based Dhamma teaching and environmental management. The findings highlight a direct alignment between these skills and specific United Nations' Sustainable Development Goals (SDGs). The identified skills contribute significantly to achieving inclusive education, sustainable economic growth, resilient infrastructure, responsible consumption, environmental protection, and the promotion of peaceful societies. In conclusion, this research emphasizes the importance of cultivating a diverse skill set among Thai Buddhist moral teacher monks, offering valuable insights for policymakers, educators, and religious institutions seeking to enhance leadership capabilities and align efforts with global sustainability objectives.